Child and Adolescent Development for Medical Learners: Lines of Development - Florence Eddins-Folensbee; Jason Scott Klein; Sheila Renee Martinez; Roland Wickes Folensbee; Toi Blakely Harris (Association of American Medical Colleges, 2012)
Abstract This resource focuses on lines of development as related to children and adolescents and is one of six modules that addresses child and adolescent development. Other topics covered in additional modules include: developmental neurobiology, developmental framework and early development, identity development, context of development, and developmental perspectives of emotion and illness. Each module uses teaching tools which include learning objectives, lecture outline, lecture text, clinical correlations or case vignettes, sample test questions, recent related research, after-class exercises or activities, audiovisual aids including some dedicated teaching clips or transcripts, bibliographies, and PowerPoint presentations. These can be used together as a complete course or independently by topic. This module consists of three lecture packets titled: Cognitive Development, Moral Development, and Psychosexual Development. For each lecture a PowerPoint presentation and lecture text/outline are provided. A list of suggested discussion topics and supplemental readings is also provided.